A history of medieval philosophy - Copleston, F. C. (Methuen, 1972)
In this classic work, Frederick C. Copleston, S.J., outlines the development of philosophical reflection in Christian, Islamic, and Jewish thought from the ancient world to the late medieval period. A History of Medieval Philosophy is an invaluable general introduction that also includes longer treatments of such leading thinkers as Aquinas, Scotus, and Ockham.